Leading across boundaries : creating collaborative agencies in a networked world - Linden, Russell Matthew (Jossey-Bass, 2010)
This second edition of the bestselling book offers a practical guide that both explores the interpersonal and organizational forces that inhibit collaboration and offers government and nonprofit leaders the tools to combat those forces. The author provides concrete examples of both successful and unsuccessful collaborations; helps readers anticipate, prevent, and deal with the most vexing challenges to collaboration; and provides guidance on leveraging emerging trends in this field. Public managers and nonprofit organizations will find a wealth of new material, updated case studies, internatio.